2008
DOI: 10.4049/jimmunol.180.5.3038
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Treatment with Fms-Like Tyrosine Kinase-3 Ligand after Burn Injury Enhances Global Immune Responses to Infection

Abstract: Severely burned patients are susceptible to infections with opportunistic organisms due to altered immune responses and frequent wound contamination. Immunomodulation to enhance systemic and local responses to wound infections may be protective after burn injury. We previously demonstrated that pretreatments with fms-like tyrosine kinase-3 (Flt3) ligand (Flt3L), a dendritic cell growth factor, increase the resistance of mice to a subsequent burn injury and wound infection by a dendritic cell-dependent mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 61 publications
(50 reference statements)
4
48
0
1
Order By: Relevance
“…Flt3L is usually considered to act in synergy with other endogenous cytokines such as IL-7, IL-3 and IL-11 to stimulate B cell lymphopoiesis in vitro , with IL-12 in thymus to promote T cell development, and with IL-15 to promote NK cell development [143]. Flt3L has been shown to an effective dendritic cell growth factor and a large expansion of dendritic cells has been observed in healthy human volunteers [144], as well as mice [145] receiving Flt3L. Flt3L treatment causes a potent expansion of splenic dendritic cells, which enhances neutrophil antimicrobial functions and improves survival during burn injury and Pseudomonas aeruginosa sepsis, and the protective effect was sustained even with adoptively transferring Flt3L-treated dendritic cells [145, 146].…”
Section: Immunomodulatory Agents In Sepsis (Summarized In Table 3)mentioning
confidence: 99%
“…Flt3L is usually considered to act in synergy with other endogenous cytokines such as IL-7, IL-3 and IL-11 to stimulate B cell lymphopoiesis in vitro , with IL-12 in thymus to promote T cell development, and with IL-15 to promote NK cell development [143]. Flt3L has been shown to an effective dendritic cell growth factor and a large expansion of dendritic cells has been observed in healthy human volunteers [144], as well as mice [145] receiving Flt3L. Flt3L treatment causes a potent expansion of splenic dendritic cells, which enhances neutrophil antimicrobial functions and improves survival during burn injury and Pseudomonas aeruginosa sepsis, and the protective effect was sustained even with adoptively transferring Flt3L-treated dendritic cells [145, 146].…”
Section: Immunomodulatory Agents In Sepsis (Summarized In Table 3)mentioning
confidence: 99%
“…However, after 24 h, all mice pretreated with Flt3L died, compared to 40% of vehicle-treated mice. [20,21]. Our initial hypothesis was that Flt3L pretreatment renders mice more resistant to challenge with gut bacteria during endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…Their loss would profoundly inhibit their ability to clear the primary infection and lead to an increased propensity to bacterial translocation and secondary infections. Several investigators have reported that the enhancement of DC production could increase the resistance of mice to secondary infections [20][21][22][23], or even reverse endotoxin tolerance-related immunoparalysis [24]. Thus, we hypothesized that pre-enrichment of the LP DC pool would improve protective immunity to bacterial translocation and outcome in endotoxemic mice.…”
Section: Introductionmentioning
confidence: 94%
“…It has been reported that human skin keratinocytes and fibroblasts express Flt3-L [41]. Studies on the infection of burns in a mouse model showed that treatment with Flt3-L could lead to an enhancement of the dendritic cell number and functions, which in turn could stimulate neutrophil recruitment and function in the immune response to the infection [42][43][44]. IL-6 is mainly secreted by epidermal keratinocytes, while macrophages, Langerhans cells and fibroblasts in the dermis are the other sources in the skin [45,46].…”
Section: Discussionmentioning
confidence: 99%